The social role of archaeological heritage. The enhancement of the necropolis of Calerilla de Hortunas de Requena (Valencia, Spain) - Carrascosa Moliner, Begoña (2016)
In Europe there are three different methodologies used in the intervention and presentation techniques of in situ archaeological heritage sites: reconstructions on the archaeological remains, carried out primarily in Nordic countries; traditional presentations in the form of ruins, developed in Mediterranean countries; and hybrids, used throughout the continent. Of the three trends shown, the one that best helps meet both the needs of the enclaves and those of the public, besides offering a closer social experience, is the first methodology. In situ reconstructions of structures based on the original materials and techniques ensure its sustainability, and also help develop its social and educational purposes, which greatly facilitates their interpretation. Even though this type is scarce in Spain, fortunately, there are exceptions. The project of value enhancement of the necropolis of La Calerilla of Hortunas in Requena (Valencia, Spain) aims to be one of them.